Reducing central-line associated bloodstream infections (CLABSIs) through patient accountability contracts: A pilot project for patients on Weill Cornell Medicine (WCM) bone marrow transplant (BMT) service. Issue 28 (1st October 2022) - Garcia, Christine Ann; Taflin, Stefanie; Assalone, Dianna; Rodriguez, German; McHugh, Catherine; Whitmore, Barbara; Hatola, Christine; Calfee, David P; Shore, Tsiporah
Abstract : 283 Background: Patients with cancer whom develop Central Line Associated Blood Stream Infections (CLABSIs) have increased mortality rates ranging from 12% to 40%. Transplant patients are particularly at risk due to cytotoxic chemotherapy regimens and/or graft-versus-host disease with risk for translocation of oral and gut flora to the bloodstream. At Weill Cornell Medicine, we had 102 CLABSIs in 2021, 25 (25%) of which attributed to patients in oncology units. The Bone Marrow Transplant (BMT) Unit, had 10 of the 25 (40%), 2.05 CLABSIs per 1000 central line inpatient days with a CLABSI standardized infection ratio (SIR) of 1.26 (above goal of 1). Methods: Our SMART aim was to reduce the number and rate of CLABSI events on the BMT unit by 10% from February 1, 2022 – June 30, 2022 by educating patients on preventive strategies and implementing a patient central-line maintenance "contract." We had previously optimized evidence-based nursing interventions for CLABSI prevention which included adherence to central line maintenance best practices, weekly device rounds with Infection, Protection & Control to monitor compliance with dressing changes and IV tubing, annual CLABSI prevention competencies, peer-to-peer validation of blood culture lab draws, weekly quality-improvement huddles and interdisciplinary root cause analysis discussions for CLABSI events. Patient noncompliance with daily recommendations for central line care was identified as a possible CLABSI risk factor that was not previously addressed in the bundle. Newly-developed patient education and a "contract" was incorporated into the BMT admission process. Results: The BMT CLABSI patient education and contract was initiated with all new patients admitted to unit in February 1, 2022. Since starting, the BMT unit CLABSI SIR has decreased from 1.26 to 0.6, and from a CLABSI rate per 1000 central lines days of 2.05 to 0.97. Conclusions: Engaging patients in their own care of the central lines can significantly reduce overall risk of central line infections. Patients have positively responded to this pilot project. We have translated educational materials and contracts to other languages and are considering expansion into other units.